2024
DOI: 10.7759/cureus.54019
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Healing: Embracing the Triple Bottom Line Approach in Post-pandemic Healthcare

Mairy Alim,
Saanie Sulley

Abstract: A triple bottom line (TBL) encompasses economic, social, and environmental dimensions, which provides a strategy for transforming contemporary healthcare systems. This study contextualized current TBL developments in healthcare under the spotlight of COVID-19 pandemic-related challenges and opportunities. The paper has five sections, including an introductory section that outlines the TBL concept and its relevance to healthcare. Following this, we provide an overview of the three pillars of the TBL, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…This follows similar studies in other fields that confirm clear conceptual correctness and purpose [55,56]. By adopting this approach, our study advances sustainability research within the healthcare sector, which is consistent with Alim and Sulley's [78] recommendations that emphasize the need to further promote the implementation of the TBL approach and develop evaluation criteria. In consideration of the conclusions of a study of the sustainability of public hospitals in Portugal [79], which, by employing the DEA method, demonstrated that solely one healthcare organization is entirely sustainable via environmental, social, and economic perspectives, our findings acquire further significance in conjunction with all prior research.…”
Section: Discussionsupporting
confidence: 87%
“…This follows similar studies in other fields that confirm clear conceptual correctness and purpose [55,56]. By adopting this approach, our study advances sustainability research within the healthcare sector, which is consistent with Alim and Sulley's [78] recommendations that emphasize the need to further promote the implementation of the TBL approach and develop evaluation criteria. In consideration of the conclusions of a study of the sustainability of public hospitals in Portugal [79], which, by employing the DEA method, demonstrated that solely one healthcare organization is entirely sustainable via environmental, social, and economic perspectives, our findings acquire further significance in conjunction with all prior research.…”
Section: Discussionsupporting
confidence: 87%
“…17 While initially emerging in the business context, the TBL provides a three-dimensional lens of social, environmental, and economic sustainability performance and provides a framework for highly complex systems such as healthcare infrastructure. 18 As a resource-intensive industry, healthcare is pressed by cost, demand, and resource limitations.…”
Section: Sustainable Framework: the Triple Bottom Line (Tbl)mentioning
confidence: 99%
“…It poses the priority for healthcare to be sustainable. 18 Recommendations were made for better measures for deploying a TBL model for profit include cost-effectiveness and space utilization. For the people component of TBL, the measures recommended are patient satisfaction scores, outcome measures, or employee engagement levels.…”
Section: Sustainable Framework: the Triple Bottom Line (Tbl)mentioning
confidence: 99%
See 2 more Smart Citations